1997
DOI: 10.1021/jp970324i
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure and Radiation on the Luminescent Properties of Poly(vinylbenzophenone−styrene)

Abstract: High-pressure luminescence studies have been made on a polymer with a polystyrene base but with every seventh styrene converted to benzophenone (BP). The polymer was studied neat (PVBS) and in a 10% solution in polystyrene (PVBS-PS). As for BP dissolved in polymers, both photophysical and photochemical effects are observed originating from the triplet state (T 1 ). For PVBS, in addition to the phosphorescence from the monomer, an emission at lower energy occurs which we identify as an excimer and some emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…For perturbing the intermolecular interactions of polymer chains in the solid state, pressure is inherently more ideal than temperature. X-ray diffraction, infrared absorption (IR) spectra, UV/vis absorption, and fluorescence spectra of polymers have been measured under high pressure to examine the compression effects on their crystalline structures and their physical and optical properties. Recently, we reported on the relationship between pressure-induced variations in the molecular aggregation structures and the UV/vis absorption and fluorescence spectra of PIs up to 8 GPa. , Significant variations in the local excitation (LE) and intermolecular CT absorption bands and fluorescence intensity were separately observed for nonfluorescent and highly fluorescent PI films up to 1 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…For perturbing the intermolecular interactions of polymer chains in the solid state, pressure is inherently more ideal than temperature. X-ray diffraction, infrared absorption (IR) spectra, UV/vis absorption, and fluorescence spectra of polymers have been measured under high pressure to examine the compression effects on their crystalline structures and their physical and optical properties. Recently, we reported on the relationship between pressure-induced variations in the molecular aggregation structures and the UV/vis absorption and fluorescence spectra of PIs up to 8 GPa. , Significant variations in the local excitation (LE) and intermolecular CT absorption bands and fluorescence intensity were separately observed for nonfluorescent and highly fluorescent PI films up to 1 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure is a more suitable factor than temperature in perturbing the intermolecular interactions of polymer chains in the solid state. X-ray diffraction, infrared absorption (IR) spectra, UV/visible absorption and the fluorescence spectra of polymers have been measured under high pressure to examine the compression effects on their crystalline structure, and on their physical and optical properties. For instance, Lorenzen et al reported variations in the bulk compressibility of crystalline poly(tetrafluoroethylene) (PTFE) by increasing the pressure using X-ray diffraction patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Convington et al , measured the pressure-induced shifts of the infrared absorption modes of poly(methyl methacrylate) (PMMA) and polycarbonate (PC), and they concluded that most of the free volume was removed after compression up to 2 and 1 GPa, respectively. Drickermer et al ,, reported variations in the steady-state and time-dependent emission properties of neat polymer and polymer blends. Erskine et al measured pressure-induced variations in the optical transmission spectra of PMDA/ODA PI up to 12 GPa, and concluded that intermolecular CT transitions exist in the PI because a significant bathochromic shift of the absorption edges was caused by applying pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure is a more ideal external stimulus compared with temperature for perturbing the aggregation structures and intermolecular interactions of polymer chains in the solid state. X-ray diffraction, infrared (IR) absorption spectra, and UV/vis absorption and fluorescence spectra of polymers have been measured under high pressure to examine the compression effects on crystalline and/or amorphous structures and variations in physical properties. For instance, Drickermer et al ,, reported variations in the steady-state and time-dependent fluorescence properties of neat polymer and polymer blends of poly[2-methoxy-5-(2′-ethylhexoxy)- p -phenylenevinylene] (MEH-PPV).…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction, infrared (IR) absorption spectra, and UV/vis absorption and fluorescence spectra of polymers have been measured under high pressure to examine the compression effects on crystalline and/or amorphous structures and variations in physical properties. For instance, Drickermer et al ,, reported variations in the steady-state and time-dependent fluorescence properties of neat polymer and polymer blends of poly[2-methoxy-5-(2′-ethylhexoxy)- p -phenylenevinylene] (MEH-PPV). Guha et al , observed the fluorescence spectra and Raman scattering of polyfluorene under high pressure.…”
Section: Introductionmentioning
confidence: 99%